The Effect Of Health Promotion Through Whatsapp Social Media On Knowledge young Women About Personal Hygiene With Symptoms Of Vaginitis In SMP Negeri 02 Class IX Panyabungan Mandailing Natal In 2025 - Desi, Ferika (Sean Institute, 2025)
Adolescent girls have a vulnerability to vaginitis if they do not maintain vaginal hygiene Vaginitis occurs in women who have entered the puberty phase or will enter the menopausal phase with risk factors in the form of lack of hygiene, unprotected sexual relations, with multiple partners, sexually transmitted diseases and others. Personal Hygiene needs to be considered because it is related to the incidence of genitalia infections. The most common vaginitis is bacterial vaginosis, Trichomoniasis and vulvovaginal candidasis. This study aims to determine whether there is an influence of health promotion through whatsapp social media on the knowledge of grade IX adolescent girls about personal hygiene with symptoms of vaginitis at SMP 02 Kelas IX Panyabungan Kabupaten Mandailing Natal Tahun 2025. The type of research used is Pre-Experimental research. The population in the study is all grade IX adolescent girls at SMP Negeri 02 Kelas IX Panyabungan Kabupaten Mandailing Natal Tahun 2025. The sampling technique uses purposive sampling with a sample size of 41 people. Using the Wilcoxon test. The results of the study obtained the average knowledge before (7,561) and after (12,048). Wilcoxon test results obtained p value = 0.000 < 0.05 which shows there is an influence after being given health promotion through whatsapp social media about personal hygiene in adolescents at SMP Negeri 02 Kelas IX Panyabungan Kabupaten Mandailing Natal Tahun 2025 WhatsApp social media can be used as a reference for modern learning in conveying information to provide health promotion about personal hygiene with symptoms of vaginitis in adolescents to increase knowledge so that adolescents are prevented from diseases of the vagina